Role of Leptin in the Digestive System - Kim, Min-Hyun; Kim, Hyeyoung (Frontiers in Pharmacology, 2021)
Leptin is a pluripotent peptide hormone produced mainly by adipocytes, as well as by other tissues such as the stomach. Leptin primarily acts on the central nervous system, particularly the hypothalamus, where this hormone regulates energy homeostasis and neuroendocrine function. Owing to this, disruption of leptin signaling has been linked with numerous pathological conditions. Recent studies have also highlighted the diverse roles of leptin in the digestive system including immune regulation, cell proliferation, tissue healing, and glucose metabolism. Of note, leptin acts differently under physiological and pathological conditions. Here, we review the current knowledge on the functions of leptin and its downstream signaling in the gastrointestinal tract and accessory digestive organs, with an emphasis on its physiological and pathological implications. We also discuss the current therapeutic uses of recombinant leptin, as well as its limitations.